2016
DOI: 10.1102/2051-7726.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

Does monitor position influence visual-motor performance during minimally invasive surgery?

Abstract: Background: In minimally invasive surgery (MIS), the natural relationship between hand and eye is disrupted, i.e. surgeons typically control tools inserted through the patient's abdomen while viewing the workspace on a remote monitor, which can be located in a variety of positions. This separates the location of visual feedback from the area in which a motor action is executed. Previous studies suggest that the visual display should be placed directly ahead of the surgeon (i.e. to preserve visual-motor mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Demonstrable success in improving standards has come from the aviation industry – where flight simulators have contributed to drastic improvements in safety – and the military . In health care, and specifically surgery, computer simulation has become increasingly prevalent as a means of training clinicians, evaluating competency and as a tool for reducing errors . Dentistry is relatively unique amongst healthcare specialities in that it has a long history of using simulators in training .…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrable success in improving standards has come from the aviation industry – where flight simulators have contributed to drastic improvements in safety – and the military . In health care, and specifically surgery, computer simulation has become increasingly prevalent as a means of training clinicians, evaluating competency and as a tool for reducing errors . Dentistry is relatively unique amongst healthcare specialities in that it has a long history of using simulators in training .…”
Section: Introductionmentioning
confidence: 99%
“…al, in which they performed a previous study aiming to quantify the effects of the VMFD problem in image-guided surgery. 1 We plan to expand our system to display both US and Fluoroscopy and create a customizable workflow for endoleak repair, a procedure which typically requires both US and Fluoroscopy for guidance. Using either hand gestures or voice commands, the clinician will be able to swap seamlessly between modalities and position the displays in their desired location, without worry about interference from the C-Arm, ceiling-mounted monitor, or US machine.…”
Section: Discussionmentioning
confidence: 99%
“…Often, due to lack of space, the clinician have to perform a procedure with the display in a sub-optimal position, increasing the visual motor field disparity (VMFD) already inherently present in imageguided procedures. 1 Without adequate visualization of the imaging displays, procedure time and radiation dose increase, targeting accuracy decreases, and the overall ability to perform a safe and successful procedure is jeopardized.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of endoscopic skill learning have consistently shown that the visual display should be placed directly ahead of the operator to preserve visual-motor mapping. 16 The monitor is sheathed in a sterile drape with clear window after the screen protective cover has been peeled off.…”
Section: How To Do Itmentioning
confidence: 99%